2015
DOI: 10.3917/poeu.046.0008
|View full text |Cite
|
Sign up to set email alerts
|

Analyser l'exportation des normes au-delà de l'Union européenne

Abstract: Distribution électronique Cairn.info pour L'Harmattan. © L'Harmattan. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The focus on these areas shed light on new facets of Europeanization, revealing that it also occurs through forms of emulation when states or regions voluntarily allow Europeanization to take over their norms and policies (Barbé and Johannsson Nogués, 2008). Other authors have shown that the export of norms and values abroad represents a mix of international and European norms (Petiteville, 2006;Tulmets, 2014b). In other words, the EU is not always a source of change, and is also one among many others.…”
Section: The Eu's External Action: Enlargement Neighbourhood and Regmentioning
confidence: 99%
See 3 more Smart Citations
“…The focus on these areas shed light on new facets of Europeanization, revealing that it also occurs through forms of emulation when states or regions voluntarily allow Europeanization to take over their norms and policies (Barbé and Johannsson Nogués, 2008). Other authors have shown that the export of norms and values abroad represents a mix of international and European norms (Petiteville, 2006;Tulmets, 2014b). In other words, the EU is not always a source of change, and is also one among many others.…”
Section: The Eu's External Action: Enlargement Neighbourhood and Regmentioning
confidence: 99%
“…Against this backdrop, a few scholars investigated under which conditions EU norms are or are not transferred to countries geographically close to the EU, especially to those participating in the ENP (Featherstone and Kazamias, 2001;Buzogányi and Costa, 2009;Wolczuk and Langbein 2012;Delcour, 2013). While early works tended to opt for an institutionalist approach and the transfer of 'hard' norms in a hierarchical or unilateral way, further analyses also considered the transfer of 'soft' norms, benchmarks, knowledge and ways of behaving in a more horizontal or transnational approach (Sedelmeier, 2001;Tulmets, 2005aTulmets, , 2005bTulmets, , 2010Tulmets, , 2014bNoutcheva, 2008). Current work sheds light on the domestic reasons of non-Europeanization (cf.…”
Section: The Eu's External Action: Enlargement Neighbourhood and Regmentioning
confidence: 99%
See 2 more Smart Citations
“…This chapter aims at exploring the conditions by which international organizations are able to act as "conveyor belts" through which norms are diffused to national contexts, with a particular focus on how such norms are transferred from the European Union to countries participating in the European Neighbourhood Policy. It will start with a definition of the concept of norms, followed by a conceptual clarification, since the research on norm diffusion is divided into various disciplines and analytical approaches that have little interaction with each other (Tulmets, 2014a;Delcour & Tulmets, 2019). In order to better grasp the overarching characteristics and mechanisms behind norm diffusion, a second section of this chapter will look particularly at two different traditions that have attracted considerable scholarly attention: Europeanization and policy transfer studies.…”
Section: Chapter 1 -International Institutions and Norm Diffusionmentioning
confidence: 99%